Presupuesto una herramienta fundamental para la proyección financiera de las PYMES en Colombia. (2022)
I will start this article highlighting a phrase from the manager of the firm CR Consulters Mauricio Reyes; “A budget will be effective to the extent that it helps us make decisions and that it can be monitored with the execution of operations” and insists that “The ability to build the budget is refined over time, but you have to do the best effort” (2019) Within the planning of the budgets, the objectives that are intended to be met in the future must be included, the regulations that must be carried out, the measures and action plans, some indicators and define those responsible for develop each task, regardless of whether it is a small, medium or micro company (MIPYMES), which is why entities such as Bancolombia bank affirm that one of the most common errors in budgeting occurs when only the general manager or the sales manager makes these projections individually, they also recommend that the best option is to do them with the whole team covering the most general vision of the possible c changes and what is expected to be obtained in the future.